A reference genome and methylome for the Plasmodium knowlesi A1-H.1 line. Issue 3 (March 2018) - Benavente, Ernest Diez; de Sessions, Paola Florez; Moon, Robert W.; Grainger, Munira; Holder, Anthony A.; Blackman, Michael J.; Roper, Cally; Drakeley, Christopher J.; Pain, Arnab; Sutherland, Colin J.; Hibberd, Martin L.; Campino, Susana; et al.
Graphical abstract: Highlights: Plasmodium knowlesi A1-H.1 line has been successfully adapted to continuous culture in human erythrocytes. A reference genome for the PkA1-H.1 line has been assembled using state-of-the-art technology. The new reference genome has improved characterisation of kir and SICAvar genes. It provides additional overall genome coverage when mapped onto by clinical sample short reads. Potential PkA1-H.1 methylation sites are characterised. Abstract: Plasmodium knowlesi, a common parasite of macaques, is recognised as a significant cause of human malaria in Malaysia. The P. knowlesi A1H1 line has been adapted to continuous culture in human erythrocytes, successfully providing an in vitro model to study the parasite. We have assembled a reference genome for the PkA1-H.1 line using PacBio long read combined with Illumina short read sequence data. Compared with the H-strain reference, the new reference has improved genome coverage and a novel description of methylation sites. The PkA1-H.1 reference will enhance the capabilities of the in vitro model to improve the understanding of P. knowlesi infection in humans.